Patterns of longitudinal medical treatment of pediatric patients ever-diagnosed with attention deficit hyperactive disorder: A community-based, retrospective, naturalistic study. (October 2022) - Ben Shoham, Assaf; Shefer, Galit; Tsafrir, Shlomit
Background: Pharmacological treatment for ADHD exhibits much variation. Longitudinal prescription-filling trajectories are interesting objects to explore. The goal of this study is to identify distinct patterns of longitudinal prescription filling among pediatric patients who were ever diagnosed with ADHD. Methods: Longitudinal data of ADHD-specific prescription filling during 2010–2019 of children diagnosed with ADHD during 2000–2019 who were 4–17-years-old at the time of diagnosis was obtained. Clustering of prescription-filling vectors was performed using K-means. Results: Analysis of 57, 110 prescription vectors yields five distinct patterns: high intensity treatment, from early childhood to late teens (5.7%); moderate intensity, from early childhood to late teens (13.3%); high intensity, from late childhood to late teens (6.1%); moderate intensity, from late childhood to late teens (14.2%); and low intensity, sporadic treatment (60.7%). These patterns correspond with observed clinical presentations. Conclusions: Identifying longitudinal prescription-filling patterns substantiates and qualifies the variation in long-term efficacy of pharmacological treatment for ADHD in a treatment-as-usual community setting. Prescription-filling implies that symptoms are present, and that treatment is efficacious, as perceived by parents' and carers. Prolonged pharmacological treatment was perceived to have had a positive net value for 40% of the children, which under appropriate reservations, provides weak evidence of efficacy.